Maths software in the learning of calculus for student of the Universidad Nacional Intercultural de la Amazonía - Angulo-Romero, Adolfo (2019)
In engineering, mathematics is a tool to solve problems, being the basis of the professional profile. However, there are few tools in college for optimal learning, being a challenge for university teaching. Within an Amazonian context, in the Universidad National Intercultural de la Amazonia, the research problem emerged How does influences the maths software application in Learning Calculus I in Indigenous students in the second cycle of Career Agroforestry Aquaculture Engineering? The objective was to determine the influence of the application of mathematical software in the learning of these students, with a sample 40 students of 2nd semester. The design was two groups. Tests of knowledge were used, evaluated before and after application of the Software. The data were compared using Student t test for paired samples (α = 0.05). The results indicated that there was significant difference in learning Calculus I, and therefore the application of the software had a positive effect on indigenous engineering students. There was learning differences between indigenous and mestizo students before the implementation of the Software but no significant differences among the indigenous groups at the end of the implementation of mathematical Software. The application of Software and hours of practice were decisive in the learning of calculus I. Finally, there were significant differences between the learning of students at the end of the implementation of Software College Precalculus Solved.